MEKTEP OQÍWSHÍLARÍNA EKOLOGIYALÍQ TÁLIM HÁM TÁRBIYA KÓNLIKPELERIN QÁLIPLESTIRIWDE GEOGRAFIYA PÁNINIŃ ÁHMIYETI - Nurlanov, A.S. (SCIENCE and SOCIETY, 2024)
Due to the drying up of the Aral Sea, the ecological disaster on the territory of the Republic of Karakalpakstan has aggravated and led to negative changes in the environment, and significantly affected all sectors of the economy. This article considers the role of geography in the formation of environmental education and skills in schoolchildren of Karakalpakstan.